The Effect Of Consumer Engagement And Vividness In Tiktok Marketing Content On Re-Purchase Intention Among Generation Z In The City Of Bengkulu - Rike Sepliana; Ermy Wijaya; Sri Handayani (Utami Publisher, 2026)
Consumer Engagement and Vividness in TikTok Marketing Content are important factors that can influence consumer Re-Purchase Intention. The higher the level of customer engagement and the clarity of a strong marketing video, the greater the likelihood of consumers making a purchase. The purpose of this study is to examine whether there is an influence between Consumer Engagement and Vividness in TikTok Marketing Content on Re-Purchase Intention among Generation Z in Bengkulu City. This study focuses on social media commerce on the TikTok platform. Based on the characteristics of the study, a sample of 100 respondents was obtained using the nonprobability sampling method. The research analysis used multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between Consumer Engagement on Re-Purchase Intention among Generation Z in Bengkulu City. Because t count is greater than t table (3.155> 1.660) with a significant value of 0.002 <0.05, which means Ha is accepted and H0 is rejected. There is a positive and significant influence between Vividness in Tiktok Marketing Content on Re-Purchase Intention among Generation Z in Bengkulu City. Because t count is greater than t table (7,551> 1,660) with a significant value of 0.001 <0.05 which means Ha is accepted and H0 is rejected. There is a positive and significant influence between Consumer Engagement and Vividness in Tiktok Marketing Content together (simultaneously) on Re-Purchase Intention among Generation Z in Bengkulu City. Because F count is greater than F table (122,926> 3.09) with a value (Sig) of 0.001 <0.005. The results of multiple linear regression have the equation Y = 5.367 + 0.263X1 + 0.627X2 + e. Because the regression direction is positive, it can be interpreted that if Consumer Engagement and Vividness increase, Re-Purchase Intention in generation Z in Bengkulu City will also increase.